THE AUTHORITY TO FILE BANKRUPTCY PETITIONS AFTER THE ESTABLISHMENT OF INDONESIA’S FINANCIAL SERVICES AUTHORITY - Erma Defiana Putriyanti (Fakultas Hukum Universitas Gadjah Mada, 2015)
The transfer in the functions, duties, and authority for regulation and supervision as stipulated in Article 55 of the Act concerning the Financial Services Authority (OJK) does not include the transfer of authority in filing a petition for bankruptcy. The authority to file a bankrupty petition against a debtor in the financial services sector still refers to Article 2 paragraph (3) to (5) Act No. 37 of 2004 concerning Bankruptcy and Suspension of Payment. Peralihan fungsi, tugas dan kewenangan pengaturan dan pengawasan sebagaimana dimaksud dalam Pasal 55 Undang-undang tentang Otoritas Jasa Keuangan (OJK) tidak termasuk peralihan kewenangan pengajuan pailit. Kewenangan untuk mengajukan permohonan pailit terhadap debitor yang bergerak dibidang jasa keuangan tetap mengacu pada Pasal 2 ayat (3) sampai (5) Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU.